Design and Build an IoT-Based Shoe Dryer Monitoring and Control System - Apriandi Alfa Reza Saragih; Pardede, A M H; Simanjuntak, Magdalena (Yayasan Kita Menulis, 2024)
Wet shoes that are not dried immediately can lead to the growth of bacteria and fungi that can potentially damage the shoes and cause health problems in the user. Therefore, an effective and efficient shoe dryer is needed. This research aims to design and develop a monitoring and control system for shoe dryers based on the Internet of Things (IoT) that can be operated remotely through a web-based application or mobile device. The system consists of several main components, namely humidity and temperature sensors, microcontrollers, wireless communication modules, and heating elements. Humidity and temperature sensors are used to detect the condition of the shoe and the surrounding environment, while the microcontroller is in charge of processing the data and regulating the operation of the heating element as needed. With the wireless communication module, users can monitor and control the drying process in real-time through an application connected to the internet.